Mapping of prehaustorial resistance against wheat leaf rust in einkorn (Triticum monococcum), a progenitor of wheat - Deblieck, Mathieu; Ordon, Frank; Serfling, Albrecht (Frontiers in Plant Science, 2023)
Wheat leaf rust (Puccinia triticina) is one of the most significant fungal diseases of wheat, causing substantial yield losses worldwide. Infestation is currently being reduced by fungicide treatments and mostly vertical resistance. However, these measures often break down when the fungal virulence pattern changes resulting in a break down of vertical resistances. In contrast, the prehaustorial resistance (phr) that occurs in the einkorn-wheat leaf rust interaction is race-independent, characterised by an early defence response of plants during the prehaustorial phase of infestation. Einkorn (Triticum monococcum) is closely related to Triticum urartu as a progenitor of wheat and shows generally a high level of resistance against leaf rust of wheat. Hence, Einkorn can serve as a valuable source to improve the level of resistance to the pathogen in future wheat lines. In particular, einkorn accession PI272560 is known to exhibit a hypersensitive prehaustorial effector triggered immune reaction, preventing the infection of P. triticina. Remarkably, this effector triggered immune reaction turned out to be atypical as it is non-race-specific (horizontal). To genetically dissect the prehaustorial resistance (phr) in PI272560, a biparental F2 population of 182 plants was established after crossing PI272560 with the susceptible T. boeoticum accession 36554. Three genetic maps comprising 2,465 DArT-seq markers were constructed and a major QTL was detected on chromosome 5A. To locate underlying candidate genes, marker sequences flanking the respective QTL were aligned to the T. urartu reference genome and transcriptome data available from the parental accessions were used. Within the QTL interval of about 16.13 million base pairs, the expression of genes under inoculated and not inoculated conditions was analysed via a massive analysis of cDNA (MACE). Remarkably, a single gene located 3.4 Mbp from the peak marker within the major QTL was upregulated (20 to 95-fold) after the inoculation in the resistant accession in comparison to the susceptible T. boeoticum accession. This gene belongs to a berberine bridge enzyme-like protein that is suspected to interact on the plant surface with glycoside hydrolases (GH) secreted by the fungus and to induce a hypersensitive defence reaction in the plant after fungal infections.